THE ROLE OF XENOBIOTIC BIOTRANSFORMATION IN THE DEVELOPMENT OF LIVER DISEASES IN OCCUPATIONAL EXPOSURE TO VINYL CHLORIDE - O. A. Dyakovich (Acta Biomedica Scientifica)
The production of polyvinyl chloride has currently acquired a special significance because of the widespread using of polymeric materials based on it in many industries. Vinyl chloride is a monomer of polyvinyl chloride, which is considered extremely dangerous and highly carcinogenic to humans. This article provides a brief review of the literature on the role of bio transformation system in functional disorders of the liver in PVC production workers. We describe the first and second phases of the biotransformation of lipophilic xenobiotics in the human body, for example, vinyl chloride. The data on gene polymorphism of enzymes involved in the metabolism of vinyl chloride (isoform of cytochrome P450 - CYP2E1, glutathione transferase GSTM1 and GSTT1) were presented in this article. The results of experimental studies of the effect of vinyl chloride on the state of the biotransformation of xenobiotics were reflected. This article examined the factors affecting the activity of the system in terms of the production of vinyl chloride exposure - age, smoking and alcohol.